TRADITIONAL INJUNCTIONS AND COMMERCIAL REAL ESTATE DEVELOPMENT IN ABAK, AKWA IBOM STATE, NIGERIA - Ekpo, Mbosowo Ebong; Bassey, Nse Akpan (Western European Studies, 2023)
The study aimed at examining the effect of traditional injunction on commercial real estate development in Abak local government area of Akwa Ibom State. In order to achieve the stated aim, the following objectives were set; to identify the reasons for the placement of traditional injunctions on developments in the study area and to ascertain the effect of traditional injunction on commercial real estate development in the study area. The study adopted the survey design method. The research population comprised village heads and property developers in the study area. The study employed simple random sampling technique to obtain a sample size of 175. Descriptive statistics was used in the analysis of the data obtained. The study found that the major reason of placement of traditional injunction on proposed developments in the study area was to arrange for and promote co-existence between strangers and indigenes of the community with the highest mean value of 4.33. it was also found out that respondents with mean values of 4.19 each, attested to the fact that the reason was to generate revenue and to use the generated revenue for infrastructural development in the community. The study also revealed that placement of traditional injunction on proposed development delays the development period as well as increases the cost of development in the study area. This study was necessary because of the dynamic nature of emerging property markets of developing nations such as Nigeria. Investors may wish to evaluate the impact of traditional injunction on property developments. This study is unique as it gathered historical data which the results could serve as a guide to property investors in making investment decisions.
Keywords: Traditional institutional arrangement; commercial; real estate